2022 17th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2022
DOI: 10.1109/hri53351.2022.9889535
|View full text |Cite
|
Sign up to set email alerts
|

Having the Right Attitude: How Attitude Impacts Trust Repair in Human—Robot Interaction

Abstract: Robot co-workers, like human co-workers, make mistakes that undermine trust. Yet, trust is just as important in promoting human-robot collaboration as it is in promoting human-human collaboration. In addition, individuals can significantly differ in their attitudes toward robots, which can also impact or hinder their trust in robots. To better understand how individual attitude can influence trust repair strategies, we propose a theoretical model that draws from the theory of cognitive dissonance. To empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…To that end, Kohn and colleagues [64] found that apologies worked better to regain trust than a system denying an error. However, Esterwood and Robert [34] could show that promising no errors in the future as well as explanations for why the error happened showed greater effects than mere apologies (see also results by [136]). In contrast to that, Robinette et al [112] and Schelble et al [116] found no effects of apologies on trust repair.…”
Section: Results Of the Trust Calibration Interventionsmentioning
confidence: 96%
See 1 more Smart Citation
“…To that end, Kohn and colleagues [64] found that apologies worked better to regain trust than a system denying an error. However, Esterwood and Robert [34] could show that promising no errors in the future as well as explanations for why the error happened showed greater effects than mere apologies (see also results by [136]). In contrast to that, Robinette et al [112] and Schelble et al [116] found no effects of apologies on trust repair.…”
Section: Results Of the Trust Calibration Interventionsmentioning
confidence: 96%
“…Screening of dangerous objects/subjects [4, 14, 15, 19, 36, 51, 54-56, 85, 94, 107, 117], detection of system malfunctions [89,90], crime prevention [10], recidivism prediction [132], watch a video of a house search [66,83] Transportation Responding to take-over requests [2, 6, 7, 47, 61, 68-70, 77, 84, 98], collusion avoidance [8], managing (air) traffic [31,118], pedestrians interaction with AV [48], observe AVs [64,119], drive in driving simulator [87,96,136] Military Screening tasks [17,33,44,63,81,82,127,130,135,139,140], gathering of information [58], mission planning [92], human-AI collaboration for search and destroy missions [116] Production Improving production [73,133,143], disassembly [5], moving objects [34,35,45], demand forecasting [39], harvesting [113], quality checks [142] Gaming trust game [3,23], collaboration game [24], flanker task…”
Section: Security and Safetymentioning
confidence: 99%
“…Outpatient clinics consistently serve as crucial windows for patients seeking medical care. However, the introduction of informatic robots, while enhancing efficiency, potentially erodes the essential trust inherent in healthcare interactions [ 6 ]. Patients may understandably harbor reservations about entrusting their care trajectory to a mechanized entity, potentially leading to discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the participants did not value apologies and denials because it was not supported by behavioral change, an effect found in interpersonal trust literature (Schweitzer et al, 2006) and in the human-robot literature (Luo et al, 2021). Other trust repair strategies that could be more effective with machine advice include an expression of regret that accompanies the apology (Kox et al, 2021), delaying the repair strategy until the next trust opportunity (Nayyar & Wagner, 2018;Robinette et al, 2015), providing promises or explanations that reduce cognitive dissonance between initial attitudes and experiences (Esterwood & Robert, 2022), or adding human-like qualities to expression of the trust repair strategy (de Visser et al, 2016;Kim & Song, 2021).…”
Section: Discussionmentioning
confidence: 99%